Knot of this world - Marks, Mary (Marks, Mary. Quilting mystery., 2020)
Quilter Martha Rose must patch together the clues to solve the murder of a cult leader in the California mountains ... Has Martha's fellow quilter and dear friend Birdie Watson become unraveled' Birdie and her new husband have decided to join the Mystical Feather Society, a spiritist group living on a commune in the mountains of Ojai, California. Before her free-spirited friend makes a huge mistake, Martha organizes a surprise visit to check out the commune. While white-robed members conduct a seance in a glass yurt, their leader'Royal St. Germain'is nowhere to be found ... until, that is, Martha and her friends discover him shot in their Winnebago. Now Martha must track down the killer and debunk the cult'before it's bye bye Birdie ...